PENGUJIAN HUKUM WAGNER DALAM PEREKONOMIAN INDONESIA KAJIAN PENGELUARAN PEMERINTAH PUSAT DAN PEMERINTAH PROVINSI - Ni Made Sukartini; Samsubar Saleh (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2012)
This study tried toconduct a study such as testing whether Wagner's Law applies in the Indonesian economy. The study is divided into the study at the central and provincial governments. Wagner Law be interesting tostudy, since there are many variations of the specifications used in previous studies and there varaisi finding whether the law is valid or not in a country. Most of the studies conducted in developed countries, and yet manystudies conducted in developing countries. Therefore, it is interesting to conduct a study for the case of developing countries like Indonesia. The study concluded that Wagner's Law applies partially at the level of thecentral government and the provincial government. There are limitations to the data series has a perfect causality test can not be met. The study concluded that in the case of routine expenditure and developmentexpenditure, Wagner laws apply as predicted, that the increase in government spending to respond to an increase in income per capita.Key words: Wagner law, government spending, income per capita, Indonesia